Outcome of repeated multi-stage arthroplasty with custom-made acetabular implants in patients with severe acetabular bone loss: a case series - Fröschen, Frank Sebastian; Randau, Thomas; Hischebeth, Gunnar T R; Gravius, Nadine; Wirtz, Dieter Christian; Gravius, Sascha; Walter, Sebastian (HIP international, 2020)
Background: Failed reconstruction in cases of severe acetabular bone loss, with or without pelvic discontinuity, in revision total hip arthroplasty (rTHA) remains a great challenge in orthopaedic surgery. The aim of this study was to describe the outcome of a “second” rTHA with “custom-made acetabular components (CMACs)” after a previously failed reconstruction with CMACs. - Methods: 4 patients with severe acetabular bone loss (Paprosky Type IIIB), who required a second rTHA after a previously failed reconstruction with CMAC, due to prosthetic joint infection (PJI), were included in our retrospective study. All prostheses had been constructed on the basis of thin-layer computed-tomography scans of the pelvis. The second rTHA was considered unsuccessful in the event of PJI or aseptic loosening (AL) with need for renewed CMAC explantation. - Results: The treatment success rate after second rTHA with a CMAC was 50% (2 of 4). In the successful cases, the visual analogue scale (VAS) score and Harris Hip Score (HHS) after the second rTHA (VAS range 2-4; HHS range 45-58 points) did not differ from those after the first rTHA, before onset of symptoms (VAS: range 2-4; HHS: range 47-55 points). In the failed cases, the second CMACs needed to be explanted due to PJI, with renewed detection of previous pathogens. Patients with treatment failure of the second CMAC had required a higher number of revision surgeries after explantation of the first CMAC than patients with a successful outcome. - Conclusions: In patients with severe acetabular bone loss and previously failed rTHA with CMACs, repeat rTHA with a CMAC may be a solid treatment option for patients with an “uncomplicated” multi-stage procedure, i.e., without persisting infection after explantation of the original CMAC. While the outcome in terms of clinical function does not appear negatively affected by such a “second attempt,” the complication rate and risk of reinfection, nonetheless, is high.
Gesehen am 22.12.2025